2011
DOI: 10.1093/chrsci/49.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Stir Bar Sorptive Extraction with Polyurethane Foams for the Determination of Testosterone and Methenolone in Urine Matrices

Abstract: This work describes the development, validation, and application of a novel methodology for the determination of testosterone and methenolone in urine matrices by stir bar sorptive extraction using polyurethane foams [SBSE(PU)] followed by liquid desorption and high-performance liquid chromatography with diode array detection. The methodology was optimized in terms of extraction time, agitation speed, pH, ionic strength and organic modifier, as well as back-extraction solvent and desorption time. Under optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The PU foams proposed were shown to be a promising, advantageous polymeric phase, when compared with SBSE(PDMS), using both sampling modes (HS and immersion) to monitor priority targets having a wide range of polarity (e.g., triazinic herbicides and metabolites in water, roasted coffee volatiles, acidic pharmaceuticals and hormones in biological fluids) [65][66][67].…”
Section: Alternative Phases or Microextraction Techniquesmentioning
confidence: 99%
“…The PU foams proposed were shown to be a promising, advantageous polymeric phase, when compared with SBSE(PDMS), using both sampling modes (HS and immersion) to monitor priority targets having a wide range of polarity (e.g., triazinic herbicides and metabolites in water, roasted coffee volatiles, acidic pharmaceuticals and hormones in biological fluids) [65][66][67].…”
Section: Alternative Phases or Microextraction Techniquesmentioning
confidence: 99%
“…Meanwhile, the operative error is hard to be avoided. In order to simplify the pretreatment procedure and improve the method sensitivity, some new techniques such as molecular imprinted polymer solid phase extraction (SPE) [25,26], solid phase microextraction (SPME) [27], stir bar microextraction (SBME) [28] and online SPE [29,30], have also been applied to determine AAS in diverse biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…All samples were extracted, purified and analyzed as before. It was indicated that the recovery of all meat or egg/milk samples was above 90% (Table 4), higher than that in previous study 14 . The high recovery of methenolone may be attributed to the optimized sample preparation and HPLC‐MS/MS determination process.…”
Section: Resultsmentioning
confidence: 65%
“…In another study, LC‐MS/MS was used to directly detect the glucuronide‐conjugated metabolite of methenolone in human urine with a LOD at 1.0 ng/ml and a high recovery rate of 95% 13 . Sequeiros et al 14 developed an HPLC method by stir bar sorptive extraction using polyurethane foams with a lower LOD (0.2 ng/ml) but a less recovery (54.2%). Further, Guo et al 8 improved the LC‐MS/MS method by using Turboflow C18‐P SPE for purification, and better sensitivity (LOD, 0.01 ng/ml; low limit of quantification [LOQ], 0.1 ng/ml) was obtained for the online testing of human urine samples.…”
Section: Introductionmentioning
confidence: 99%